Formação e preservação do acervo fotográfico do Instituto Histórico e Geográfico de Vila Velha (IHGVV): memórias, testemunhos e o patrimônio canela-verde - Miguel, Marcelo Calderari (2024)
Our research focuses on how the development and maintenance of the photo archive at the Historical and Geographical Institute of Vila Velha (IHGVV) help safeguard the shared history of Vila Velha (ES). The main goal of this research is to examine how the IHGVV's photo collection was created and maintained to safeguard the town's shared history. The study focuses on how collective memory influences the maintenance of photo collections in information Science, describes the process of formation and consolidation of this collection, diagnoses the preservation strategies used and evaluates the IHGVV's performance in preserving collective memory, from their early stages to their current objectives. The foundation of this concept lies in the social and collective aspects of memory, as discussed by Maurice Halbwachs and Pierre Nora. The research utilizes a qualitative method, focusing on exploring and describing the IHGVV case study. The methodology involves examining the bibliographic review, making a documentary analysis of meeting minutes, observing employees' operational guidelines and interviews to understand the management practices of the iconographic collection of this public utility institution. It has been found that the IHGVV's visual repository is essential for protecting the shared and emotional memories of Vila Velha, with the intention of reinforcing the cultural ties within the society and securing intergenerational availability to a tradition that respects the past and unifies various age groups. The research highlights successful conservation methods that can be employed in other museum and archival organizations, and suggests specific actions for the expansion, dissemination and mediation of this collection. For optimal preservation and accessibility of the image collection, it is advised to introduce Computerized Archival Management Systems and Reliable Digital Archival Repositories (RDC-Arq). Their responsibility is to ensure the legitimacy, confidentiality, availability, and perpetuation of these documents, while also improving the public's access to the city's collective past. This research highlights the importance of integrated archival management strategies and public policies that value the history of institutions such as IHGVV, which aid in the ongoing effort of cultural preservation.